Divine hiddenness, the demographics of theism, and mutual epistemic dependence: a response to Max Baker-Hytch - Blanton, Andrew (Religious studies, 2025)
In his article "Divine Hiddenness and the Demographics of Theism" Stephen Maitzen (2006) develops a permutation of the argument from divine hiddenness which focuses on the uneven distribution of theistic belief around the globe. Max Baker-Hytch (2016) responds to this argument by providing a theodicy which appeals to the fact that humans are epistemically interdependent. In this article I argue that Baker-Hytch's response is at best incomplete and at worst relies on a faulty modal judgement. After exploring some ways Baker-Hytch might salvage his theodicy and maintaining their failure, I conclude with the success of Maitzen's argument.